Profil Kemampuan Pemecahan Masalah Matematis Materi Aritmatika Sosial Berdasarkan Teori Polya Ditinjau dari Self-Confidence Siswa SMP - Rita Nurkhalipah; Ramlah Ramlah; Attin Warmi (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2020)
This study aims to describe mathematical problem solving abilities in terms of students' self-confidence. This is motivated by the number of students who have low self-confidence in solving mathematical problem solving problems. The research used a qualitative approach to the case study method with the subject as many as 3 students of class VII of one of the state junior high schools in Karawang district, using tests in the form of questions to describe their problem-solving abilities, self-confidence questionnaires and interviews. The data analysis technique used data reduction, display data, and conclusion drawing or verification. Based on the results of data analysis, it was showed that self-confidence are high and solving problems, it is be able to meet the stages of understanding problems, compiling plans, and implementing plans. Students with low self-confidence show that they do not meet any of the problem solving stages. So, it can be concluded that the ability to solve mathematical problems in terms of students' self-confidence in social arithmetic material, no one student can re-examine the results in the Polya stage.